OPTIMASI MATEMATIS KEUNTUNGAN HOME INDUSTRY PIA IBU SANDRA DI TOMBATU UTARA - Gabriel E. W. Mosey; James U. L. Mangobi; Marvel G. Maukar (LPPM Universitas Bina Bangsa, 2023)
In the industrial sector, problems are often found in optimizing production results in order to obtain maximum profits. Pia home industry Mrs. Sandra has a problem in maximizing profits, namely finding solutions to produce pia with the optimal amount. The purpose of this study was to determine the amount of production and optimal profit obtained in the production of pia in the home industry using the branch and bound method and to determine the results of the sensitivity analysis to changes in production components. The results of the analysis show that using the branch and bound method, the home industry pia Mrs. Sandra gets an optimal profit of Rp. 2,078,557 per month by producing 1,666 pia chocolate, 1,041 pia temo, and 800 pia peanuts per month. The results of the sensitivity analysis show that profits will remain in optimal conditions if Mrs. Sandra's pia home industry follows the changes that occur in production components based on the upper bound and lower bound according to the output produced using Lingo 19.0 software